2016
DOI: 10.1371/journal.pone.0167172
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between Zein and Lecithin in Ethanol-Water Solution and Characterization of Zein–Lecithin Composite Colloidal Nanoparticles

Abstract: Lecithin, a naturally small molecular surfactant, which is widely used in the food industry, can delay aging, enhance memory, prevent and treat diabetes. The interaction between zein and soy lecithin with different mass ratios (20:1, 10:1, 5:1, 3:1, 2:1, 1:1 and 1:2) in ethanol-water solution and characterisation of zein and lecithin composite colloidal nanoparticles prepared by antisolvent co-precipitation method were investigated. The mean size of zein-lecithin composite colloidal nanoparticles was firstly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(40 citation statements)
references
References 36 publications
6
34
0
Order By: Relevance
“…By comparing the spectrum of WPI with encapsulated DIM, peaks of Amid I were shifted from 1640 cm −1 to 1647, 1666, and 1667 cm −1 , with different ratios of DIM in WPI, indicating the presence of an electrostatic interaction between WPI and DIM rather than the chemical reactions. Therefore, it is concluded that the interaction of WPI and DIM is based on electrostatic forces [49]. An increase in the intensity of Amid I and Amid II also suggests the binding of DIM to β-lactoglobulin; similar results were revealed by Wang et al [30].…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…By comparing the spectrum of WPI with encapsulated DIM, peaks of Amid I were shifted from 1640 cm −1 to 1647, 1666, and 1667 cm −1 , with different ratios of DIM in WPI, indicating the presence of an electrostatic interaction between WPI and DIM rather than the chemical reactions. Therefore, it is concluded that the interaction of WPI and DIM is based on electrostatic forces [49]. An increase in the intensity of Amid I and Amid II also suggests the binding of DIM to β-lactoglobulin; similar results were revealed by Wang et al [30].…”
Section: Resultsmentioning
confidence: 53%
“…Hydrogen bonding and hydrophobic interaction maybe the main forces related to the interaction of whey protein and hydrophobic substances [30]. Several characteristic peaks due to C–H stretching of the aliphatic group were observed at 2970, 2983, 2970, and 2980 cm −1 in the spectra of microencapsulated DIM with different ratios [14,49]. Amid I and Amid II bands are considered as the backbone of whey protein isolate, confirming the presence of α-lactalbumin and β-lactoglobulin, which are the main constituents of whey protein isolate.…”
Section: Resultsmentioning
confidence: 99%
“…35 For this reason, the influence of the temperature on the various zein nanoparticles was investigated. The surfactant-free formulation showed a considerable increase of size and polydispersity index when it was heated, while the zeta potential analysis provided negative values (Table 3).…”
Section: Effect Of Heatingmentioning
confidence: 99%
“…In the case of ionic strength and pH, these nanoparticles have been shown to be highly liable to aggregation at a low concentration of sodium chloride (NaCl), and to be unstable at pH above 5. The salt added to formulations increases the ionic strength, with consequent increases in van der Waals interactions and hydrophobic effects among the protein chains, favoring aggregation and precipitation of the proteins (Dai et al, 2016 ). Similar findings have been reported in other studies (Patel et al, 2010 ).…”
Section: Colloidal Stability Of Zein Nanoparticlesmentioning
confidence: 99%